Mô hình dòng điện xích đạo từ số liệu vệ tinh CHAMP - Thanh, Lê Trường; VAFI, DOUMOUYA; Minh, Lê Huy; Châu, Hà Duyên (Vietnam Journal of Earth Sciences, 2012)
SUMMARYThe equatorial electrojet model with champ satellite dataThe EEJ (Equatorial Electrojet) is a complex current system flowing in the ionospheric E-layer. Its value changes in space and in local time. The magnetic signature of the EEJ overlaps on the recorded magnetic data and the amplitude of the EEJ magnetic signature is very small with respect to that of the main field. So the separation of the EEJ magnetic is difficult. Today, we have many kinds of data for studying EEJ (ionosonde, rocket, magnetic observatories...). Many results of the studies of EEJ were publicated, but these resultsare with some limit as there are few data from obsevation and the data are no regularly distributed.The CHAMP satellite has launched from July 15, 2000. It gives the good data for studying the EEJ because of its low orbit and passing along the longitudes, crossing the equator at noon time.In this paper we introduce the CHAMP satellite, its recorded data and give an algorithm for separating the EEJ magnetic signature from the total magnetic field. We present the application of this method to the data received in 2003, with 158 quiet days, about 1345 values of total field around noon (for local time from 10 to 14 hour) to study the EEJ. An empirical model of the EEJ, including local time,longitude, latitude is also presented in this paper; we try to apply the EEJ data for one year 2003 to define some parameters of EEJ around the world.